Comparaison de l`évaluation subjective et objective des blessures au dos des athlètes d`élite de taekwondo - Park, K. J. (Science & Sports, 2024)
Objectives This study sought to determine the relationship between the subjective evaluation of the low back pain scale and Modified Oswestry Disability Index (MODI) and the objective evaluation of muscle function and recovery period for elite Taekwondo players with back pain injuries.